Modifiable risk factors for dementia, and awareness of brain health behaviors: Results from the Five Lives Brain Health Ireland Survey (FLBHIS) - Dukelow, Tim; Lawrence, Erin Grace; Jacobson, Liron; Vassilev, Philip; Koychev, Ivan; Muhammed, Kinan; Kennelly, Sean P. (Frontiers in Psychology, 2023)
Up to 40% of dementias globally are attributable to modifiable risk factors. Many existing studies examining attitudes to brain health are limited by a failure to consider a range of pertinent risk factors and associated barriers to protective behaviors. In Ireland, self-reported knowledge of dementia is poor compared to other conditions. In this context, the current study aimed to explore exposure to and awareness of specific modifiable risk factors for dementia. We also aimed to investigate whether exposure to these risk factors is associated with demographic and socioeconomic factors. A cross-sectional survey was administered to 555 voluntary participants in February 2022. The survey captured the following information: (1) Sociodemographic factors; (2) Exposure to, as well as knowledge of modifiable risk factors for dementia, namely diet, social interaction, exercise, hypertension, sleep, depression, smoking, alcohol consumption, cognitive stimulation, hearing impairment, diabetes, air pollution, and head injury. The study population comprised 551 participants (50.3% male; 49.6% female). Mean age was 59.7 years. Modifiable risk factors for dementia were prevalent. Relative to females, male gender was significantly associated with multiple risk factors. Whilst 65.6% of participants believed that lifestyle improvements can decrease a person’s risk of developing dementia, only 31.4% believed that dementia could be prevented. Head injury (90.9%, n = 500), low mental stimulation (85.3%, n = 469), and alcohol consumption (77.8%, n = 428) were the three most commonly recognized risk factors. Awareness was significantly greater in both university groups (undergraduate and postgraduate) for multiple risk factors. Our findings demonstrate that the distribution of exposure to modifiable risk factors for dementia is unequal across gender and age groups, and that awareness levels vary across risk factors. These findings highlight that focus surrounding dementia prevention should shift toward individual risk profiling and should be tailored toward an individual’s specific needs.